2016
DOI: 10.18203/issn.2455-4510.intjresorthop20160711
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparative study between trochanteric versus piriformis entry portal for intramedullary interlock nailing in the treatment of femoral shaft fracture

Abstract: <p class="abstract"><strong>Background:</strong> In case of close nailing for femoral shaft fractures, the nail is inserted into the medullary cavity through the proximal femur without disturbing the periosteal blood supply of at the fracture site. The piriformis fossa and greater trochanter has been commonly described as starting points for antegrade femoral nailing. The purpose of this study was to compare results of two entry ports being used for intramedullary nailing for femoral shaft fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, given the limited resources, it is nearly impossible to offer early fixation for isolated femur shaft fractures in our setting. The median operating time of our study (195 minutes) was also comparatively longer than the reported durations for antegrade nailing (71 to 116 minutes) [2,[23][24][25] probably due to poor resources such as the limited availability of the C arm for surgeries. However, the rate of surgical site infections (3 out of 46) was comparable to the previous studies [23,24].…”
Section: Discussionmentioning
confidence: 63%
“…However, given the limited resources, it is nearly impossible to offer early fixation for isolated femur shaft fractures in our setting. The median operating time of our study (195 minutes) was also comparatively longer than the reported durations for antegrade nailing (71 to 116 minutes) [2,[23][24][25] probably due to poor resources such as the limited availability of the C arm for surgeries. However, the rate of surgical site infections (3 out of 46) was comparable to the previous studies [23,24].…”
Section: Discussionmentioning
confidence: 63%
“…Osteosynthesis of the femur using an intramedullary nail is considered to be the gold standard for treating diaphyseal fractures of the femur. This is considered to be superior to extramedullary fixation using plates and external fixators, from both the biomechanical and the clinical points of view 2 . Intramedullary nail provides predictable restoration of shaft length and alignment and allowed early load bearing.…”
Section: Introductionmentioning
confidence: 99%